A water-soluble fraction from a by-product of wheat increases the formation of propionic acid in rats compared with diets based on other by-product fractions and oligofructose - Lina Haskå; Roger Andersson; Margareta Nyman (Food & Nutrition Research, 2011)
Dietary fibre is fermented by the colonic microbiota to carboxylic acids (CA), with potential health effects associated in particular with butyric and propionic acid.To investigate the formation of CA in the hindgut of healthy rats fed dietary fibre from different fractions of wheat shorts, a by-product of the milling of wheat.Rats were fed dietary fibre (80 g/kg feed per day for 7 days) from wheat shorts and fractions thereof (ethanol-soluble, water-soluble and insoluble fractions), oligofructose (OF) diet and a mixture of oligofructose and raffinose (OR) diet.The water-soluble fraction, with a high content of arabinoxylan (AX), increased the formation of propionic acid in the hindgut and lowered the ratio of acetic to propionic acid in the portal blood of rats. High levels and proportions of butyric acid were seen in rats fed the OR diet. The pattern of CA resulting from the ethanol-soluble diet, mainly composed of fructan and raffinose, was more similar to that of the OF diet than the OR diet.The high formation of propionic acid with the water-soluble fraction may be attributed to the high AX content. The results also indicate that the wheat fructans produced more propionic acid and less butyric acid than OF. It may furthermore be speculated that the formation of butyric acid associated with the OR diet was due to a synergetic effect of OR.